A Review of Countermovement and Squat Jump Testing Methods in the Context of Public Health Examination in Adolescence: Reliability and Feasibility of Current Testing Procedures - Petrigna, Luca; Karsten, Bettina; Marcolin, Giuseppe; Paoli, Antonio; D’Antona, Giuseppe; Palma, Antonio; Bianco, Antonino (Frontiers in Physiology, 2019)
Background: In the context of public health physical fitness examination in adolescence, countermovement jump (CMJ) and squat jump (SJ) are two vertical jumps tests widely used to evaluate lower limb muscle strength and power respectively. The main criticism of both the CMJ and SJ test is the lack of test standardisation. Therefore, the objectives of this review were: a) to gather information about both jumps; b) to investigate whether it is possible to identify common procedures referred to the CMJ and SJ technical execution, and c) to design Standard Operating Procedures (SOPs) to promote CMJ and SJ standardization in an adolescent population aged 12-18 years. Methods: The review partially adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement(PRISMA). Due to the growing attention in monitoring physical health through field tests in recent years, articles were collected through PubMed, Web of Science and Scopus databases from January 2009 to July 2019. Original articles in which CMJ or SJ were used to assess muscular strength in adolescents were eligible for further analysis. The English language was imposed as a limit. Results: A total of 117 studies met the inclusion criteria. The description of the CMJ and SJ test procedures was different within the literature, with discrepancies in the jump technique, number of jumps, and measurement devices used. Conclusions: A lack of method standardisation for both the CMJ and the SJ test was identified. Based on the literature, SOPs for both vertical jumps were proposed. These are useful in the context of public health physical fitness examination in adolescents,as they facilitate an unbiased comparison of jump performance data between published studies.